SMART-Teen: An Educational and Mentoring Program to Enhance HIV/AIDS Prevention among Adolescents - Ilmiatus Qoyimah; ainun khoiriya (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2026)
Adolescents are vulnerable to HIV/AIDS-related risk behaviors due to limited knowledge, misconceptions, peer influence, and inadequate access to accurate health information. Educational interventions and mentoring programs are important strategies to improve adolescents’ awareness and preventive behaviors. The SMART-Teen (Student Movement for Awareness, Resilience, and Prevention against HIV/AIDS) program was developed as a community service initiative to strengthen HIV/AIDS prevention among adolescents. This community service program employed a participatory educational and mentoring approach involving 120 adolescents from five SMA/MA/SMK institutions in Tuban Regency, East Java, Indonesia. The intervention was implemented over five days and included educational sessions, group discussions, case-based learning, educational games, and peer mentoring activities. Pre-test and post-test assessments were conducted to evaluate changes in participants’ knowledge and attitudes regarding HIV/AIDS prevention. The findings demonstrated an improvement in participants’ knowledge and attitudes following the intervention. The mean knowledge score increased from 62.4 ± 10.8 before the intervention to 86.7 ± 8.3 after the intervention. Participants also demonstrated increased awareness and reduced misconceptions regarding HIV/AIDS prevention. The SMART-Teen program effectively improved adolescents’ knowledge and awareness regarding HIV/AIDS prevention through educational and mentoring strategies.